Molten carbonate fuel cells for CO2 separation and segregation by retrofitting existing plants – An analysis of feasible operating windows and first experimental findings. (April 2015) - Rexed, I.; della Pietra, M.; McPhail, S.; Lindbergh, G.; Lagergren, C.
Highlights: Molten carbonate fuel cells and combustion flue gas. Operating window with low CO2 concentration at the cathode. Molten carbonate fuel cells lab scale experimental study. Abstract: Molten carbonate fuel cells (MCFC) used as active carbon dioxide concentrator units are a promising solution to reduce greenhouse gas (GHG) emissions from traditional combustion plants. The cell reaction transfers carbonate ions from the cathode to the anode and allows the fuel cell to simultaneously produce power and separate CO2 from a stream of flue gas. Carbon dioxide separation is of high interest for use in natural gas combined cycles and coal gas combustion plants, as a large part of anthropogenic CO2 worldwide originates from such installations. The flue gas from these types of combustion technologies typically contains 3–15% CO2, which is in the lower operational range of the MCFC. The aim of this work was to investigate the possibility to retrofit existing power plants with MCFC to reduce the total release of CO2 without necessarily reducing the power output, and to understand which kind of power plant could have the major benefits with an MCFC retrofitting. The performance of lab scale MCFC fed with simulated flue gas was evaluated, and a number of operational parameters, such as utilization factor and cathode humidification were varied to study the effect on fuel cell performance. The results show that it is feasible to operate the MCFC as a CO2 separator for simulated gas turbine flue gas; however, the voltage drop due to low CO2 concentration may restrict the operating window depending on various operating conditions.